Country-Specific CO2 and Non-CO2 Emission Factor for Coal Electricity Generation in Malaysia - R. Ahmad, Radin Diana; Kamil Abdullah,; Sazalina Zakaria,; Raja Shazrin Shah Raja Ehsan Shah,; YuanJi Mok,; Nik Meriam Sulaiman, (International Journal of Integrated Engineering, 2024)
Malaysia’s national greenhouse gas (GHG) emissions inventory for electricity generation utilises the default GHG emission factor values from the 2006 Intergovernmental Panel on Climate Change (IPCC) Guidelines. Electricity generation is the key source of GHG emissions; hence, improvement in the emissions assessment through developing country-specific emission factors (EF) will increase the accuracy and further reduce the uncertainty of reported national GHG emissions. In 2019, the uncertainty of the total inventory without Land Use, Land-Use Change and Forestry (LULUCF) was ±15.12%, and the uncertainty in trend was ±12.70%, which is in the higher range. Thus, this study analysed 2017-2019, carbon dioxide (CO2), methane (CH4) and nitrous oxide (N2O) emission factors from the stationary combustion of coal-fired power plants to develop the representative country-specific emission factor of the coal used in Malaysia using the fuel analysis and flue gas method. This study also supplements an assessment of relevant country-specific oxidation factors. The results indicate that the weighted average of each year for the CO2 emission factor of Bituminous coal is lower than IPCC default values from 93,078 kgCO2/TJ to 93,224 kgCO2/TJ, whilst Sub-Bituminous coal averages from 96,260 kgCO2/TJ to 96,714 kgCO2/TJ and Lignite coal higher than the IPCC values, from 101,720 kgCO2/TJ to 105,116 kgCO2/TJ. In deriving the emission factor, the carbon content was lowest for Bituminous coal, followed by Sub-Bituminous coal, and significantly higher for Lignite coal. The CO2 emission factors values analysed are 1% lower for bituminous coal and 1% to 4% higher for sub-bituminous coal and lignite compared with 2006 IPCC Guidelines default values. For Bituminous, the calculated emission factor of CH4 is 0.1011 kgCH4/TJ and N2O is 0.7047 kgN2O/TJ. As for Sub-Bituminous, the calculated CH4 emission factor is 0.0883 kgCH4/TJ whilst for N2O is 0.9516 kgN2O/TJ. The emission factor for Lignite’s CH4 is 0.0402 kgCH4/TJ and N2O is 0.5563 kgN2O/TJ respectively. The coal CH4 and N2O emission factors are lower than the Tier-1, fuel-based method suggested by the IPCC. The significant variations for coal depend on the differences between the producing regions and characteristics, chemical properties, and annual fluctuations in fuel quality. This study has shown that emission factors changed due to the variations of coal used by the power plant, either due to the carbon content or calorific value. This fact certainly will influence the decision-making process, affecting the choice of coal used in the power plants that will be included in future national energy systems.